2019
DOI: 10.1073/pnas.1820744116
|View full text |Cite
|
Sign up to set email alerts
|

Arg302 governs the pK a of Glu325 in LacY

Abstract: Lactose permease is a paradigm for the major facilitator superfamily, the largest family of ion-coupled membrane transport proteins known at present. LacY carries out the coupled stoichiometric symport of a galactoside with an H+, using the free energy released from downhill translocation of H+ to drive accumulation of galactosides against a concentration gradient. In neutrophilic Escherichia coli, internal pH is kept at ∼7.6 over the physiological range, but the apparent pK (pKapp) for galactoside binding is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 35 publications
2
16
0
Order By: Relevance
“…Most recently, side chains in the vicinity of Glu325 were mutated with the rationale that interaction with Glu325 should alter its pK a . Remarkably, only mutant R302K of the sites tested causes the pK a to decrease and by over 2 pH units, thereby lending further support to the idea that H + is displaced from Glu325 by spatial fluctuations in the position of Arg302 moving near Glu325 or vice versa (40). The possibility will be tested with a suppressor t-RNA approach using arginine homologs with side chains of varied lengths (43).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Most recently, side chains in the vicinity of Glu325 were mutated with the rationale that interaction with Glu325 should alter its pK a . Remarkably, only mutant R302K of the sites tested causes the pK a to decrease and by over 2 pH units, thereby lending further support to the idea that H + is displaced from Glu325 by spatial fluctuations in the position of Arg302 moving near Glu325 or vice versa (40). The possibility will be tested with a suppressor t-RNA approach using arginine homologs with side chains of varied lengths (43).…”
Section: Discussionmentioning
confidence: 77%
“…close to Glu325 (∼6 Å), are unable to catalyze active transport but exhibit transmembrane exchange (38), and evidence has been presented (39,40) in support of the idea that H + may be extracted from Glu325 by spatial fluctuations in the position of Arg302 that expel H + by moving near Glu325 or vice versa.…”
Section: Discussionmentioning
confidence: 78%
“…Compatible with this flexible design of membrane-embedded substrate-and H + -binding sites, neither D34 in MdfA nor the drug/H + stoichiometry is conserved within the DHA1 subfamily 51 . By contrast, in the substrate-specific LacY, the substrate/ H + coupling relies on the extensive and intricate H-bonding networks, as such, the precise positioning of H + -and substrate-binding amino acids is essential for the transport function 11,46 . Therefore, the substrate/H + coupling mechanism of LacY lacks flexibility and the substrate/H + stoichiometry is fixed.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the coupling between substrate-and H + -binding in the H + -dependent LacY is highly specific, which depends on the dense and precise networks of H-bonds implicated in substrate-and H + -binding. Therefore, the substrate/H + coupling in LacY is intolerant to the alteration of amino acids involved in these H-bonding interactions 10,11 . Apparently, the exact chemical structure of the LacY substrate imposes stringent structural restraints on the substrate/H + coupling mechanism 8 .…”
mentioning
confidence: 99%
“…In neutrophilic E. coli , the internal pH is kept at ~ 7.6 over the physiological range, but the apparent p K (p K app ) for galactoside binding is 10.5 [5]. Surface‐enhanced infrared absorption spectroscopy (SEIRAS) demonstrated that the high p K a is due to Glu325 (helix X), which must be protonated for LacY to bind galactoside effectively [6,10]. The microenvironment of this residue is shown in Fig.…”
Section: Figmentioning
confidence: 99%